'Nothing but humiliation for Russia': Moscow and NATO's eastern enlargement, 1993-1995. Issue 6 (9th November 2020) - Radchenko, Sergey
ABSTRACT: This article recounts Russia's response to NATO's eastern enlargement. It argues that NATO enlargement was seen as perfectly acceptable in Moscow, as long as it was inclusive of Russia, which would gain in status as America's key partner and ally. Once it became apparent that Russia would not be invited to join, the narrative changed to active opposition, as Boris Yeltsin sought domestic legitimacy from being perceived as thedefender of the national interest against Western encroachment. The article highlights the fluid nature of so called national interests, which are defined and redefined in ways affording the greatest legitimation to the political elites.